Aspects of Medieval Japanese Religion - Bernard R. Faure; Andrea Castiglioni (Religions, 2022)
The focus of this Special Issue is on medieval Japanese religion. Although Kamakura “new” Buddhist schools are usually taken as unquestioned landmarks of the medieval religious landscape, it is necessary to add complexity to this static picture in order to grasp the dynamic and hybrid character of the religious practices and theories that were produced during this historical period. This Special Issue will shed light on the diversity of medieval Japanese religion by adopting a wide range of analytical approaches, encompassing various fields of knowledge such as history, philosophy, materiality, literature, medical studies, and body theories. Its purpose is to expand the interpretative boundaries of medieval Japanese religion beyond Buddhism by emphasizing the importance of mountain asceticism (Shugendō), Yin and Yang (Onmyōdō) rituals, medical and soteriological practices, combinatory paradigms between local gods and Buddhist deities (medieval Shintō), hagiographies, religious cartography, conflations between performative arts and medieval Shintō mythologies, and material culture. This issue will foster scholarly comprehension of medieval Japanese religion as a growing network of heterogeneous religious traditions in permanent dialogue and reciprocal transformation. While there is a moderate amount of works that address some of the aspects described above, there is yet no publication attempting to embrace all these interrelated elements within a single volume. The present issue will attempt to make up for this lack. At the same time, it will provide a crucial contribution to the broad field of premodern Japanese religions, demonstrating the inadequacy of a rigid interpretative approach based on sectarian divisions and doctrinal separation. Our project underlines the hermeneutical importance of developing a polyphonic vision of the multifarious reality that lies at the core of medieval Japanese religion.